Needs and quality of life of people with middle-stage dementia and their family carers from the European Actifcare study. When informal care alone may not suffice. (3rd July 2018) - Kerpershoek, Liselot; de Vugt, Marjolein; Wolfs, Claire; Woods, Bob; Jelley, Hannah; Orrell, Martin; Stephan, Astrid; Bieber, Anja; Meyer, Gabriele; Selbaek, Geir; Handels, Ron; Wimo, Anders; et al.
ABSTRACT: Objective: The Actifcare (Access to timely formal care) study investigated needs of people with dementia and their families during the phase in which formal care is being considered, and examined whether higher need levels are related to lower quality of life (QOL). Method: From eight European countries 451 people with dementia and their carers participated. Needs were measured with the Camberwell Assessment of Need for the Elderly. QOL was measured with the QOL-AD, and carer quality of life was measured with the CarerQol. The relationship between needs and QOL was analysed with multiple regression analyses. Results : Needs were expressed in the domains of psychological distress, daytime activities, company and information. People with dementia rated their unmet needs significantly lower than their carers: the mean number of self-rated unmet needs was 0.95, whereas the mean proxy ratings were 1.66. For met needs, the self-rated mean was 5.5 and was 8 when proxy-rated. The level of needs reported was negatively associated with QOL for both. Conclusion : The study results show that informal carers reported almost twice as many needs as people with dementia. The domains in which needs are expressed should be the primary focus for interventions to support   QOL. The perspectives of people with dementia are informative when identifying needs.